MicroRNA‐374 inhibits proliferation and promotes apoptosis of mouse melanoma cells by inactivating the Wnt signalling pathway through its effect on tyrosinase. Issue 8 (17th June 2019) - Li, Xiao‐Jing; Li, Zhi‐Feng; Xu, Yan‐Yan; Han, Zhao; Liu, Zhi‐Jun
Abstract: Melanoma is one of the most malignant skin tumours with constantly increasing incidence worldwide. Previous studies have demonstrated that microRNA‐374 (miR‐374) is a novel biomarker for cancer therapy. Therefore, this study explores whether miR‐374 targeting tyrosinase (TYR) affects melanoma and its underlying mechanism. We constructed subcutaneous melanoma models to carry out the following experiments. The cells were transfected with a series of miR‐374 mimics, miR‐374 inhibitors or siRNA against TYR. Dual luciferase reporter gene assay was used for the verification of the targeting relationship between miR‐374 and TYR. Reverse transcription quantitative polymerase chain reaction and western blot analysis were conducted to determine the expression of miR‐374, TYR, β‐catenin, B‐cell leukaemia 2 (Bcl‐2), Bcl‐2 associated X protein (Bax), Low‐density lipoprotein receptor‐related protein 6 (LRP6), Leucine‐rich repeat G protein‐coupled receptor 5 (LGR5) and CyclinD1. Cell proliferation, migration, invasion, cell cycle distribution and apoptosis were evaluated using cell counting kit‐8 assay, scratch test, transwell assay and flow cytometry respectively. TYR was proved as a putative target of miR‐374 as the evidenced by the result. It was observed that up‐regulated miR‐374 or down‐regulated TYR increased expression of Bax and decreased expressions of TYR, β‐catenin, LRP6, Bcl‐2, CyclinD1 and LGR5, along with diminished cell proliferation, migration, invasion and enhanced apoptosis. Meanwhile, cells with miR‐374 inhibitors showed an opposite trend. These findings indicated that up‐regulated miR‐374 could inhibit the expression of TYR to suppress cell proliferation, migration, invasion and promote cell apoptosis in melanoma cells by inhibiting the Wnt signalling pathway.